Hak asuh anak pasca perceraian dalam perspektif hukum Islam dan hukum positif di Indonesia - Rahman, Babur; Paripati Qomaria , Nanik (AL-MUQARANAH, 2024)
This article discusses child custody rights after divorce from the perspective of Islamic law and civil law. The provisions regarding child custody are contained in Law no. 1 of 1974, stated in article 54 paragraph (2) "That parents are obliged to look after their children until they marry or can stand on their own". In the system that has prevailed in many communities, the responsibility for caring for children is more suited to a woman. Because this is because most women with a "feminine" temperament tend to care, as if this care is natural for a woman. And based on a hadith from the Prophet sallallaahu'Alaihi wa Sallam, he said: "You have the right to take care of him as long as you have not remarried." (HR. Abu Dawud). This hadith shows that a woman (mother) has the most right to care for her child when her husband divorces her. However, the right to hadhalah does not always fall to the mother, the husband also has the right to have the same rights as the mother, if the conditions for determining the mother do not meet the criteria for providing for the child's interests, such as being apostate, having no noble character, being crazy, and so on. Because when it comes to raising children, the first thing that must be considered is the interests of the child and having the ability and ability to provide a sense of security to children who are victims of divorce.